Phase Structure of Bose - Einstein Condensate in Ultra - Cold Bose Gases - Phat, Tran Huu; Hoa, Le Viet; Hue, Dang Thi Minh (Communications in Physics, 2015)
The Bose - Einstein condensation of ultra - cold Bose gases is studied by means of the Cornwall - Jackiw - Tomboulis effective potential approach in the improved double - bubble approximation which preserves the Goldstone theorem. The phase structure of Bose - Einstein condensate associating with two different types of phase transition is systematically investigated. Its main feature is that the symmetry which was broken at zero temperature gets restore at higher temperature.